Pengaruh dimensi kualitas jasa terhadap minat mengunjungi kembali wisatawan pada objek wisata pantai carocok Painan - Karim, Haniful; Abror, Abror (Jurnal Kajian Manajemen Bisnis, 2019)
This research aims to examine the relationship between service quality dimensions and revisit intention. The population of this study is tourists who visited â€œCarocok Painan Beachâ€. This research employed 100 respondents as the samples. By using linear regression analysis, this study found that all service quality dimensions, including tangible, responsiveness, reliability, assurance and empathy have significant and positive impacts on touristâ€™s revisit intention. Furthermore, some limitations and future studies have been addressed.Keywords: Tangibles; responsiveness; reliability; assurance; empathy; revisit intention